Influence of music on maximal self-paced running performance and passive post-exercise recovery rate - Lee, S.; Kimmerly, D. S. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: The purpose of this study was to examine the influence of fast tempo music (FM) on self-paced running performance (heart rate, running speed, ratings of perceived exertion), and slow tempo music (SM) on post-exercise heart rate and blood lactate recovery rates. METHODS: Twelve participants (5 women) completed three randomly assigned conditions: static noise (control), FM and SM. Each condition consisted of self-paced treadmill running, and supine postexercise recovery periods (20 min each). Average running speed, heart rate (HR) and ratings of perceived exertion (RPE) were measured during the treadmill running period, while HR and blood lactate were measured during the recovery period. RESULTS: Listening to FM during exercise resulted in a faster self-selected running speed (10.8±1.7 vs. 9.9±1.4 km•hour-1, PCONCLUSIONS: Listening to FM during exercise can increase self-paced intensity without altering perceived exertion levels while listening to SM after exercise can accelerate the recovery rate back to resting levels.